Anita's last cha-cha - Bernardo, Singrid Andrea; Aquino, Angel; Malvar, Therese; Bordon, Jay; Quiapost Productions (Firm). ([Pace of production not identified] Quiapost Productions, 2013)
"A 12-year old Anita falls in love with the new woman in town; years later, a girlhood crush blossoms during the Fiesta of Santa Clara in Obando, Bulacan."
"Summary taken from https://www.imdb.com/title/tt3204904/?ref_=nv_sr_srsg_0
Produced by Tonee Acejo, Ferdinand Lapuz; music by Diwa de Leon; cinematography by Alma dela Pena.
Angel Aquino, Therese Malvar, Jay Bordon.
DVD
In Tagalog.
Keywords: Drama; Comedy